Analysis of the Quality of One Stop Services for Building Construction Permits (IMB) in Bogor Regency - Nurrahmah, Dina; Tuti, Retnowati Wahyuning Dyas (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
One of the bad services in Indonesia is the building permit or IMB and other related permits. In general, the One Stop Integrated Service Investment Service serves various permits, such as: IMB, Advertising Permit, Disturbance Permit, Construction Service Business Permit, and Trade Permit. In reality, there are still various criticisms and complaints from the public regarding public services provided by the One Stop Integrated Licensing Service Agency, which of course will greatly affect the image of the government in the eyes of the community. People always want to get fast, easy and cheap service. The reality is that in Bogor Regency, building permit services are still a public complaint. The fact that is happening at this time, there are still weaknesses which in general, in this case in the form of government apparatus services that have not been effective. The analysis knife used is the service theory according to Denhardt and Denhardt. This research method uses a qualitative approach with descriptive methods. The results showed that the quality of the One Stop Building Permit (IMB) Integrated Service in Bogor Regency has been running quite well, starting from adequate facilities and infrastructure starting from the strategic location of the building and can be reached by public transportation, providing satisfactory services from employees, there is an online permit arrangement and a special room for breastfeeding mothers, as a whole, the infrastructure is sufficient for the convenience of the community, but there are still shortcomings especially in the time the permit processing process is too long,